PENGARUH KOMPETENSI KEUANGAN TERHADAP LITERASI KEUANGAN BAGI WANITA DI MAKASSAR - Budi Rustandi Kartawinata; Muhammad Ikhwan Mubaraq (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2018)
Currently women hold a vital role both in business even in household. Given that the group has a very strategic position because this group becomes a determinant in decision making of household financial. Therefore, the financial literacy of women is very needed to be a guide in the financial decision making process so that the role of women can run properly and appropriately. This research aims to determine the influence of financial behavior, financial attitude, and financial knowledge on financial literacy of well educated women in Makassar city. This research is a quantitative research with descriptive and causal data analysis. Respondents studied in this research numbered to 100 well-educated women in Makassar. This study uses four variables, namely three independent variables and one dependent variable. The independent variable consists of financial behavior, financial attitude, and financial knowledge while the dependent variable is financial literacy . The results of this study indicate that the financial behavior is in the position of 73.74% and included in good category. Financial attitude has a percentage of 82.47% and included in good category. Financial knowledge has a percentage of 84.57% and included in excellent category. Financial literacy has a percentage of 78.52% and included in good category. The results of this research indicate that financial knowledge has a significant influence on financial literacy.